Supercritical impregnation and optical characterization of loaded foldable intraocular lenses using supercritical fluids. Issue 10 (October 2017) - Bouledjouidja, Abir; Masmoudi, Yasmine; Li, Yanfeng; He, Wei; Badens, Elisabeth
Abstract : Purpose : To prepare drug‐loaded intraocular lenses (IOLs) used to combine cataract surgery with postoperative complication treatment through supercritical impregnation while preserving their optical properties. Setting : Aix‐Marseille Université, CNRS, Centrale Marseille, Laboratoire de Mécanique, Modélisation & Procédés Propres, Marseille, France, and He University Eye Hospital, Liaoning Province, China. Design : Experimental study. Methods : Supercritical impregnations of commercial foldable IOLs used in cataract surgery with ciprofloxacin (an antibiotic) and dexamethasone 21‐phosphate disodium salt (an antiinflammatory drug) were performed in a noncontinuous mode. Impregnation amounts were determined through drug‐release kinetic studies. The optical characterizations of IOLs were determined by evaluating the dioptric power and the imaging quality by determining the modulating transfer function (MTF) at a specified spatial frequency according to the International Organization for Standardization (ISO 11979‐2:2014). Results : Transparent IOLs presenting an effective impregnation were obtained with a prolonged drug delivery during approximately 10 days. Optical characterizations (dioptric powers and MTF values) show preserved optical properties after supercritical treatment/impregnation. Conclusion : Supercritical treatments/impregnations do not damage the optical properties of IOLs and are therefore adequate for the preparation of delivery devices used for cataract surgery.